Organizational behavior - Newstrom, John W.
Organizational Behavior: Human Behavior at Work, 13e is a solid research-based and referenced text known for its very readable style and innovative pedagogy. While minimizing technical jargon, John Newstrom carefully blends theory with practice so that basic theories come to life in a realistic context. As in previous editions, this edition will be filled with practical, applied advice and a widely accepted, and specially updated, presentation of five models of organizational behavior that provides an integrating framework throughout the book